PHARMACOECONOMIC ANALYSIS OF EFFICACY OF DIFFERENT MODES OF ANTIBIOTIC PROPHYLAXIS IN CHOLECYSTECTOMY - A. N. Poborskiy; N. I. Ponamarev; Sh. D. Asutaev (Вестник хирургии имени И.И. Грекова, 2016)
Pharmacoeconomic assessment of efficacy of different modes of antibiotic prophylaxis was made in 27 patients with diagnosis of acute calculous cholecystitis using method of «cost-efficacy». Patients have taken ampicillin/sulbactam intravenously in the dose of 1,5 g or cephazolin intravenously in the dose 2,0 g. Medicine should be taken in 30 min. before the operation. The most expensive was antibiotic prophylaxis by cephazolin. The coefficient of «cost-efficacy» was 774,2 rubles on 1 unit of efficacy in case of cephazolin and it was 506,1 rubles on 1 unit of efficacy in other group with antibiotic prophylaxis by ampicillin/sulbactam. The authors noted the economical and clinical advantage of antibiotic prophylaxis by ampicillin /sulbactam.